Predicting debris flow pathways using volume-based thresholds for effective risk assessment - A. Rajaneesh; V. K. Krishnapriya; K. S. Sajinkumar; Nikhil Nedumpallile Vasu; Cees van Westen; Thomas Oommen; Ali P. Yunus; Vanessa J. Banks; A. P. Pradeepkumar (npj Natural Hazards)
Abstract Investigating the preferential flow path of a debris flow is crucial for quantifying the risk and developing mitigation strategies. Here, we examined 66 debris flows from the Western Ghats in India employing Rapid Mass Movement Simulation (RAMMS)::Debris Flow software to understand the kinematics of run-out. Our analysis revealed that the debris flow run-out in the study area follow two main routes: 60 along the existing stream channels (SC) and six following the steepest hill slope (SH). We further simulated these debris flows to identify their drivers, and derived a threshold that distinguishes between SC and SH-type debris flows. Our results indicate that the debris flow volumes greater than 7072 cu. m is SH-type, whereas those with smaller volumes are more likely to follow SC paths. The model’s accuracy was validated against field observations, achieving a success rate of 93% for SH-type flows and 85% for SC.